Faktor-Faktor Yang Berhubungan Dengan Budaya Keselamatan Pasien Di Rumah Sakit Karya Bhakti Pratiwi Bogor Tahun 2015 - Yasmi, Yulia (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
Adverse even (AE) in RSKBP ranged from 0.31% to 3.01% with a mortality rate of 2.22%.AE in RSKBP still considered under-reporting because most AE not reported. Building a culture of patient safety is an important element to improve patient safety and quality. This research aims to know the culture of patient safety and the factors related to the patient safety culture in RSKBP 2015. The study was conducted in March to April 2015, with a sample of 115 respondents it is Sequential explanatory research design. The data analysis with regression logistic.Patient safety culture in RSKBP still lacking. Factors related to the patient safety culture in RSKBP feedback is incident report (p = 0.021 α = 0.05, OR = 15.516) culture is not to blame (p = 0.019 α = 0.05, OR = 14.396) and a learning culture (p = 0.006 α = 0.05, OR = 0.096) .RSKBP sugest to improve patient safety culture with a comprehensive and structured efforts.